PELATIHAN KEUANGAN DALAM RANGKA MENDETEKSI FINANCIAL DISTRESS MENGGUNAKAN METODE SERVICE LEARNING & COMMUNITY DEVELOPMENT PADA KOMUNITAS STARTUP DI MALANG RAYA - Arum Prastiwi; Sari Atmini (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
The rapid growth of startups in Indonesia, particularly in the Malang Raya, continues to be accompanied by a high rate of business failure, largely due to low financial management literacy. Limited knowledge in financial management remains a major contributing factor to bankruptcy. This activity aims to enhance the understanding and skills of startup actors in detecting financial distress through financial performance assessment within the startup community in Malang Raya. The methods employed in this activity are service learning and community development, implemented through training and mentoring in the form of workshops. The workshop covers topics such as Financial Accounting Standards (SAK), Micro, Small, and Medium Entities (EMKM), cash management, and bankruptcy detection techniques, alongside practical sessions on financial statement preparation. The results of the activity show a significant increase in participants' understanding of the importance of sound financial management and early detection of financial distress. Most participants expressed high satisfaction and a strong willingness to apply the knowledge gained to the management of their businesses. These outcomes demonstrate the effectiveness of the workshop approach in strengthening startups’ financial managerial capacity, reducing bankruptcy risks, and promoting business sustainability in the Malang Raya. In conclusion, the training successfully addresses the urgent need of startup communities to improve their financial competencies. It is recommended that similar activities be conducted regularly, foster networking among entrepreneurs, and incorporate innovative financial materials to build a resilient and sustainable startup ecosystem.